2013
DOI: 10.1115/1.4025355
|View full text |Cite
|
Sign up to set email alerts
|

Review on Cell Mechanics: Experimental and Modeling Approaches

Abstract: The interplay between the mechanical properties of cells and the forces that they produce internally or that are externally applied to them play an important role in maintaining the normal function of cells. These forces also have a significant effect on the progression of mechanically related diseases. To study the mechanics of cells, a wide variety of tools have been adapted from the physical sciences. These tools have helped to elucidate the mechanical properties of cells, the nature of cellular forces, and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
182
0
6

Year Published

2016
2016
2020
2020

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 188 publications
(201 citation statements)
references
References 550 publications
(678 reference statements)
1
182
0
6
Order By: Relevance
“…Traditional techniques for studying the mechanical properties of single cells include micropipette aspiration (MPA), atomic force microscopy (AFM), optical stretching, and magnetic bead cytometry (10)(11)(12). Although these methodologies have been instrumental in elucidating the molecular basis of cellular mechanics, they require highly skilled operators and sophisticated equipment and, most importantly, suffer from low experimental throughput.…”
Section: Introductionmentioning
confidence: 99%
“…Traditional techniques for studying the mechanical properties of single cells include micropipette aspiration (MPA), atomic force microscopy (AFM), optical stretching, and magnetic bead cytometry (10)(11)(12). Although these methodologies have been instrumental in elucidating the molecular basis of cellular mechanics, they require highly skilled operators and sophisticated equipment and, most importantly, suffer from low experimental throughput.…”
Section: Introductionmentioning
confidence: 99%
“…[10][11][12] Thus, there is a pressing need for tools to define the mechanical responses of cells in 3D cultures, and a number of coupled experimental and analytical systems have been developed for this purpose. [13][14][15] These mechanobiological tools include ring-like tissue constructs, 16 tissue constructs adhered to flexible substrata 17 and 3D traction microscopy. 14 However, challenges persist for achieving displacement control, obtaining statistically significant sample sizes, avoiding diffusion barriers for soluble factors and avoiding perturbations introduced by sample handling before mechanical loading.…”
Section: Introductionmentioning
confidence: 99%
“…The second type is that of force-sensing techniques (usually used for biological cells), which seed cells onto deformable structures to measure their traction forces. Details of these techniques can be found in [4]. Generally, the choice of experimental technique is based upon what size or type of biological structure that is being investigated, what type and magnitude of loading and deformation of the material being observed, and what specific information is desired regarding that structure, i.e., microscale structures require microscale tools, whereas nanoscale structures require nanoscale tools.…”
Section: Experimental Testing For Characterisation Of Mechanical mentioning
confidence: 99%
“…Recently, advances in technology have allowed for the development of a number of different specialized techniques. A review of 45 experimental studies (based on 45 references cited in [4]) on various types of biological cells has revealed that 38% of the studies used the atomic force microscope (AFM) technique; 18% used the compression technique; 11% used microneedle technique; 9% used micropipette aspiration technique; 7% used stretch technique; and very small percentage, less than 5%, for other techniques such as particle tracking, magnetic twisting cytometry and optical tweezers. Therefore, in this paper only some of the most common and seminal techniques are reviewed and discussed.…”
Section: Experimental Testing For Characterisation Of Mechanical mentioning
confidence: 99%